Design, synthesis, molecular modelling and biological evaluation of novel 6-amino-5-cyano-2-thiopyrimidine derivatives as potent anticancer agents against leukemia and apoptotic inducers - Naglaa M. Ahmed; Mosaad S. Mohamed; Samir M. Awad; Neama A. Abd El-tawab; Mohamed S. Gaballah; Ahmed M. Said (Taylor & Francis Group, 2024)
AbstractHerein, a novel series of 6-amino-5-cyano-2-thiopyrimidines and condensed pyrimidines analogues were prepared. All the synthesized compounds (1a-c, 2a-c, 3a-c, 4a-r and 5a-c) were evaluated for in vitro anticancer activity by the National Cancer Institute (NCI; MD, USA) against 60 cell lines. Compound 1c showed promising anticancer activity and was selected for the five-dose testing. Results demonstrated that compound 1c possessed broad spectrum anti-cancer activity against the nine cancerous subpanels tested with selectivity ratio ranging from 0.7 to 39 at the GI50 level with high selectivity towards leukaemia. Mechanistic studies showed that Compound 1c showed comparable activity to Duvelisib against PI3Kδ (IC50 = 0.0034 and 0.0025 μM, respectively) and arrested cell cycle at the S phase and displayed significant increase in the early and late apoptosis in HL60 and leukaemia SR cells. The necrosis percentage showed a significant increase from 1.13% to 3.41% in compound 1c treated HL60 cells as well as from 1.51% to 4.72% in compound 1c treated leukaemia SR cells. Also, compound 1c triggered apoptosis by activating caspase 3, Bax, P53 and suppressing Bcl2. Moreover, 1c revealed a good safety profile against human normal lung fibroblast cell line (WI-38 cells). Molecular analysis of Duvelisib and compound 1c in PI3K was performed. Finally, these results suggest that 2-thiopyrimidine derivative 1c might serve as a model for designing novel anticancer drugs in the future.